2013
DOI: 10.1093/annonc/mdt293
|View full text |Cite
|
Sign up to set email alerts
|

Distinct outcome of stage I lung adenocarcinoma with ACTN4 cell motility gene amplification

Abstract: Amplification of the ACTN4 gene defines a small but substantial subset of patients with stage I lung adenocarcinoma showing a distinct outcome. Such patients require intensive medical attention and might benefit from postoperative adjuvant chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 24 publications
2
63
2
Order By: Relevance
“…High expression levels of excision repair cross-complementation group 1 (ERCC1), ribonucleotide reductase subunit M2 (RRM2), and thymidylate synthase (TS) were suggested as negative prognostic factors for patients with resected NSCLC (33,34). In addition, cyclooxygenase-2 and amplification of the actin-4 (ACTN4) gene were considered markers for a poor prognosis in stage I disease (35,36). However, a conceivable prognostic biomarker for patients with stage I AD has not yet been established.…”
Section: Univariate Analysis Multivariate Analysismentioning
confidence: 99%
“…High expression levels of excision repair cross-complementation group 1 (ERCC1), ribonucleotide reductase subunit M2 (RRM2), and thymidylate synthase (TS) were suggested as negative prognostic factors for patients with resected NSCLC (33,34). In addition, cyclooxygenase-2 and amplification of the actin-4 (ACTN4) gene were considered markers for a poor prognosis in stage I disease (35,36). However, a conceivable prognostic biomarker for patients with stage I AD has not yet been established.…”
Section: Univariate Analysis Multivariate Analysismentioning
confidence: 99%
“…Immunohistochemical staining for actinin-4 & assessment Formalin-fixed paraffin-embedded tissue specimens from resected lung adenocarcinomas were immunohistochemically analyzed with an anti-human actinin-4 monoclonal antibody (N-terminal actinin-4) (Abnova Corporation, Taipei, Taiwan) [17,22]. Immunoperoxidase staining was performed as described.…”
Section: Patient Datamentioning
confidence: 99%
“…Any lower level of immunoreactivity was classified as IHC negative. The criterion (>30%) for assessment of ACTN4 expression by IHC was defined according to the previous study in which we evaluated the expression status of ACTN4 in three independent cohorts totaling 1033 patients with stage I lung adenocarcinoma [22]. IHC results were judged independently by three investigators (H Shiraishi, Y Watabe and T Kakuya) who were unaware of the clinical data, and consensus was reached for any discordant cases.…”
Section: Patient Datamentioning
confidence: 99%
“…Although several studies have evaluated the expression levels of ERCC1 by IHC, no consensus has been reached due to the difficulty in detecting the unique functional ERCC1 isoform (41). Actin 4 has been identified as a potential prognostic biomarker in stage I lung adenocarcinoma (42). The present study revealed that ABCB1 could be used as a prognostic marker in lung ADC patients with stage I disease, and is associated with recurrence in stage I ADC patients with wild-type EGFR.…”
Section: Discussionmentioning
confidence: 66%
“…Associations between ABCB1, ALDH1A1 and CD44 expression levels and characteristics of patients with lung adenocarcinoma. 38 (81) 10 (21) 37 (79) 27 (57) 20 (43) ≥65 81 (63) 11 (14) 70 (86) 33 (41) 48 (59) 40 (49) 41 ( 13 (19) 54 (81) 27 (40) 40 (60) 39 (58) 28 (42) Female 61 (48) 7 (11) 54 (89) 16 (26) 45 (74) 28 (46) 33 ( (16) 67 (84) 27 (34) 53 (66) 47 (59) 33 (41) No 47 (37) 7 (15) 40 (85) 16 (34) 31 (66) 20 (43) 27 ( (17) 4 (10) 38 (90) 7 (17) 35 (83) 26 (62) 16 (38) 2+3 86 (83) 16 (19) 70 (81) 36 (42) 50 (58) 41 (48) 45 ( (31) 8 (20) 32 (80) 12 (30)...…”
Section: Prognostic Significance Of Abcb1 Expression In Stage Imentioning
confidence: 99%